Pyrazole-Enriched Cationic Nanoparticles Induced Early- and Late-Stage Apoptosis in Neuroblastoma Cells at Sub-Micromolar Concentrations - Guendalina Zuccari; Alessia Zorzoli; Danilo Marimpietri; Chiara Brullo; Silvana Alfei (MDPI AG, 2023)
Neuroblastoma (NB) is a severe form of tumor occurring mainly in young children and originating from nerve cells found in the abdomen or next to the spine. NB needs more effective and safer treatments, as the chance of survival against the aggressive form of this disease are very small. Moreover, when current treatments are successful, they are often responsible for unpleasant health problems which compromise the future and life of surviving children. As reported, cationic macromolecules have previously been found to be active against bacteria as membrane disruptors by interacting with the negative constituents of the surface of cancer cells, analogously inducing depolarization and permeabilization, provoking lethal damage to the cytoplasmic membrane, and cause loss of cytoplasmic content and consequently, cell death. Here, aiming to develop new curative options for counteracting NB cells, pyrazole-loaded cationic nanoparticles (NPs) (BBB4-G4K and CB1H-P7 NPs), recently reported as antibacterial agents, were assayed against IMR 32 and SHSY 5Y NB cell lines. Particularly, while BBB4-G4K NPs demonstrated low cytotoxicity against both NB cell lines, CB1H-P7 NPs were remarkably cytotoxic against both IMR 32 and SHSY 5Y cells (IC50 = 0.43-0.54 µM), causing both early-stage (66-85%) and late-stage apoptosis (52-65%). Interestingly, in the nano-formulation of CB1H using P7 NPs, the anticancer effects of CB1H and P7 were increased by 54-57 and 2.5-4-times, respectively against IMR 32 cells, and by 53-61 and 1.3-2 times against SHSY 5Y cells. Additionally, based on the IC50 values, CB1H-P7 was also 1-12-fold more potent than fenretinide, an experimental retinoid derivative in a phase III clinical trial, with remarkable antineoplastic and chemopreventive properties. Collectively, due to these results and their good selectivity for cancer cells (selectivity indices = 2.8-3.3), CB1H-P7 NPs represent an excellent template material for developing new treatment options against NB.